Adoption of Technological Products and Services for Different Consumer Profiles: An analysis using the Technology Adoption Propensity Scale - Bittencourt, Rafael; Almeida, Stefânia Ordovás de; Araujo, Clécio Falcão (Review of Business Management, 2018)
Purpose – To evaluate how different consumer profiles react to the adoption of new technologies through the replication and validation of the TAP scale in Brazil. Design/methodology/approach – We designed a descriptive study of a quantitative nature applied through a survey. Exploratory and confirmatory factorial analysis procedures were performed in order to validate the scale. We used t tests to check for statistical differences between consumer profiles. Findings – The TAP scale proved to be a valid and reliable instrument to measure technology adoption propensity among Brazilian consumers. In this group, those in a higher domain of computational innovation showed greater proficiency in the technology adoption process. In a comparison of the data from our study with those of the original one in the USA, Brazilians presented a higher propensity for technology adoption. Originality/value – The study provided advancements in three ways: 1) validating the TAP scale for Brazilian usage; 2) bringing insights to research on innovation in specific domains; 3) contributing to the studies about potential differences between developed and emergent countries related to new technology adoption and late acceptance of innovation.